IMPLEMENTASI SANKSI PIDANA PADA PERATURAN DAERAH KAWASAN TANPA ROKOK DI KOTA BANDAR LAMPUNG - Zainudin Hasan (Universitas Bandar Lampung (UBL), 2021)
Implementationof Regional Regulation No. 05 of 2018 concerningthe Non-Smoking Area of Bandar Lampung City is considered capable of helping protect andimprove public health. This of course need stobeseen how it has been implementedsofar. As forwhat will be answered in this study, how is the implementation of theRegional Regulation Number 05 of 2018 concerning the Bandar Lampung City No-Smoking Area and aspects that are obstaclestoimplementingthe regional regulation policy. The inhibiting factors in the implementation of the Regional Regulation are suchas lack of information for the public and lack offirmness in providing sanctions forviolators. Then efforts in the implementation of regional regulations, such as strategiesin supervising these regulations, as well as responsiveness in implementing theseregulations.